PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN (Studi Pelanggan Sari Roti Kota Semarang) - Yudhi Prasetyo, 12.05.51.0001; Widyasari, Suzy (Students Journal of Economic and Management, 2017)
The aim of this study was to analyze the effect of product quality, brand image and perception of the price to customer satisfaction and impact on customer loyalty cider bread in the city of Semarang. The population in this study is the customer Sari Roti in Semarang. The sample in this study as many as 100 people. The sampling technique used purposive sampling. The criteria for the samples in this study were at least 17 years and consume Sari Roti in Semarang. The analysis tool used is the test of validity, reliability and multiple linear regression. The results of the analysis can be concluded that: The product quality positively affects customer satisfaction. Brand image positively affects customer satisfaction. Perception prices positively affects customer satisfaction. Customer satisfaction has positive influence on customer loyalty Keywords: product quality, brand image perception of price, customer satisfaction and customer loyalty